Carbon source and phosphorus recovery from iron-enhanced primary sludge via anaerobic fermentation and sulfate reduction: Performance and future application - Yang, Huan; Liu, Jianyong; Hu, Peishan; Zou, Lianpei; Li, Yu-You (Bioresource technology, 2019)
[Display omitted] •AF-SR process was firstly used for carbon sources and P recovery from Fe-sludge.•Compared to control, AF-SR enhanced VFA and P release by 28.1% and 69.3%.•Based on struvite precipitation, the available VFAs was further improved by 44.5%.•A novel integrated process based on CEPS and AF-SR is proposed for application. Anaerobic fermentation and sulfate reduction (AF-SR) was firstly used for recovery of carbon sources and phosphorus from Fe-enhanced primary sludge (Fe-sludge). With FeCl3 dosage of 30 mg Fe/L, 63.0% of the chemical oxygen demand (COD) and 97.3% of the phosphorus were concentrated from sewage into Fe-sludge. Batch anaerobic fermentation tests of Fe-sludge with and without sulfate addition (AF-SR and control) were performed. The results showed that volatile fatty acid concentrations of the control and AF-SR were 211.0 and 270.2 mg COD/g volatile suspended solids, respectively. Furthermore, 33.2% (control) and 56.2% (AF-SR) of the total phosphorus in Fe-sludge was released. The recovery performances of carbon source and phosphorus were calculated based on struvite precipitation. The available carbon source of the AF-SR system was 44.5% higher than that of the control. A novel integrated wastewater and sludge treatment process based on chemically enhanced primary sedimentation and AF-SR is proposed for future application.